The arc of boxing the rise and decline of the sweet science - Silver, Mike 1945- (McFarland & Company Inc., Publisers, 2014)
"Boxing historians discuss the socioeconomic and demographic changes that have affected the quality, prominence and popularity of the sport over the past century. Chapters cover such topics as the ongoing deterioration of boxers' skills, their endurance, the decline in the number of fights and the psychological readiness of championship-caliber boxers"--Provided by publisher